use of eye-tracking in science textbook analysis: a literature review - Tóthová, Martina; Rusek, Martin (Scientia in educatione, 2021)
Contemporarily available technology has provided researchers quite an accessible method to see through students’ eyes. This offers researchers the chance to re-evaluate teaching materials from their, so far hidden, potential function’s point-of view. In this study, a literature review of research on science textbooks using the eye-tracking method is presented. Relevant journal articles or conference papers indexed on the Web of Science and Scopus databases were selected. From the original 112 papers, 18 were submitted to a thorough analysis after duplicate papers and papers not conforming to the topic were excluded. The studies’ characteristics, topics (influence of textbook design on student learning, distribution of attention, textbook effect etc.) and used methods (the device and measurement, additional methods, methodological issues) are included in the review. (Novice) science education researchers, state officers responsible for textbook evaluation, textbook authors or even teachers can profit from this overview, which clearly shows the state of the art as well as potential research directions.